Fast and straightforward analysis approach of charge transport data in single molecule junctions. (5th June 2018) - Zhang, Qian; Liu, Chenguang; Tao, Shuhui; Yi, Ruowei; Su, Weitao; Zhao, Cezhou; Zhao, Chun; Dappe, Yannick J; Nichols, Richard J; Yang, Li
Abstract: In this study, we introduce an efficient data sorting algorithm, including filters for noisy signals, conductance mapping for analyzing the most dominant conductance group and sub-population groups. The capacity of our data analysis process has also been corroborated on real experimental data sets of Au-1, 6-hexanedithiol-Au and Au-1, 8-octanedithiol-Au molecular junctions. The fully automated and unsupervised program requires less than one minute on a standard PC to sort the data and generate histograms. The resulting one-dimensional and two-dimensional log histograms give conductance values in good agreement with previous studies. Our algorithm is a straightforward, fast and user-friendly tool for single molecule charge transport data analysis. We also analyze the data in a form of a conductance map which can offer evidence for diversity in molecular conductance. The code for automatic data analysis is openly available, well-documented and ready to use, thereby offering a useful new tool for single molecule electronics.